Delinquency, substance use, and risky sexual behaviors among youth who are involved in the justice system and predominantly reside in rural communities: patterns and associated risk factors - Childs, Kristina (Journal of crime and justice, 2023)
There is a significant gap in research examining the prevalence of problem behaviors among youth involved in the juvenile justice system in rural areas. The current study sought to address this gap by exploring the behavioral patterns of 210 youth who were on juvenile probation in predominantly rural counties and who were identified as having a substance use disorder. First, we examined the correlation among 7 problem behaviors representing different forms of substance use, delinquency, and sexual risk-taking and 8 risk factors related to recent service utilization, internalizing and externalizing difficulties, and social support networks. Then, we used latent class analysis (LCA) to identify distinct behavioral profiles based on the observed problem behaviors. LCA identified a 3-class model representing distinct groups labeled Experimenting (70%), Polysubstance Use + Delinquent Behaviors (24%), and Diverse Delinquent Behaviors (6%). Finally, we assessed differences (i.e., ANOVA, χ2) in each risk factor across the behavioral profiles. Important similarities and differences in the association among the problem behaviors, behavioral profiles, and the risk factors were revealed. These findings underscore the need for an interconnected behavioral health model within rural juvenile justice systems that is able to address youths’ multidimensional needs including criminogenic, behavioral, and physical health needs.